Stem Cell Therapies for Epidermolysis Bullosa Treatment - Argyrw Niti; Georgios Koliakos; Anna Michopoulou (Bioengineering, 2023)
Epidermolysis bullosa (EB) includes a group of rare skin diseases characterized by skin fragility with bullous formation in the skin, in response to minor mechanical injury, as well as varying degrees of involvement of the mucous membranes of the internal organs. EB is classified into simplex, junctional, dystrophic and mixed. The impact of the disease on patients is both physical and psychological, with the result that their quality of life is constantly affected. Unfortunately, there are still no approved treatments available to confront the disease, and treatment focuses on improving the symptoms with topical treatments to avoid complications and other infections. Stem cells are undifferentiated cells capable of producing, maintaining and replacing terminally differentiated cells and tissues. Stem cells can be isolated from embryonic or adult tissues, including skin, but are also produced by genetic reprogramming of differentiated cells. Preclinical and clinical research has recently greatly improved stem cell therapy, making it a promising treatment option for various diseases in which current medical treatments fail to cure, prevent progression, or alleviate symptoms. So far, stem cells from different sources, mainly hematopoietic and mesenchymal, autologous or heterologous have been used for the treatment of the most severe forms of the disease each one of them with some beneficial effects. However, the mechanisms through which stem cells exert their beneficial role are still unknown or incompletely understood and most importantly further research is required to evaluate the effectiveness and safety of these treatments. The transplantation of skin grafts to patients produced by gene-corrected autologous epidermal stem cells has been proved to be rather successful for the treatment of skin lesions in the long term in a limited number of patients. Nevertheless, these treatments do not address the internal epithelia-related complications manifested in patients with more severe forms.